Assessment of pre-harvest aflatoxin and fumonisin contamination of maize in Babati District, Tanzania - Nyangi, C.; Beed, Fenton D.; Mugula, J.K.; Boni, S.; Koyano, E.; Mahuku, George S.; Sulyok, M.; Bekunda, Mateete A. (African Journal of Food, Agriculture, Nutrition and Development, 2016)
A survey was conducted in 2013 to establish total aflatoxin and total fumonisin in maize, as well as farmers’ practices relating to maize cultivation and awareness of mycotoxins, in three villages of Babati District, northern Tanzania. Quantification of total aflatoxin and fumonisin was done using enzyme-linked immunosorbent assay (Reveal AccuScan® Neogen, USA) and the results were confirmed using Liquid Chromatography Tandem Mass Spectrometer. The mean aflatoxin was 2.94 µg/kg and all samples (n=440) were within the East African Community (EAC) standard of 10 µg/kg for total aflatoxin, but the mean fumonisin was 5.15 mg/kg, more than double the EAC standard of 2 mg/kg, and 35% of samples exceeded this standard. Maize samples obtained from farmers in the village in the mid altitude, dry zone had significantly higher mean aflatoxin (3.32 µg/kg) and significantly lower mean fumonisin (3.17 mg/kg) than maize from the other two villages (in the high and mid altitude, high rainfall zones). Most farmers (n=442) were male (72%), educated to primary school level (77%) and aware of mycotoxins (62%). As well as participating in a development program, Africa Research in Sustainable Intensification for the Next Generation, most (86%) farmers had experience of working with other development programs. All farmers used flat planting, most used improved seeds (98%), ox ploughing (78%), insecticides (78%) and early planting (36%). Practices associated with mycotoxins were planting time, tillage methods, previous season planted crops, and use of insecticides. Awareness of mycotoxins and climatic conditions were also associated with mycotoxin prevalence. In conclusion, good practices are associated with acceptable aflatoxin levels and should be continued. However, the high level of fumonisins warrants further investigation.